Правові засади необхідних для ОПК України реформ в умовах кризи - Семенишин, А. В. (НДІ ПЗІР НАПрН України, 2014)
У статті проаналізовано господарсько-правові заходи реформування ОПК України в умовах кризової ситуації в економіці України з урахуванням викликів, які постають унаслідок зовнішньої військової агресії проти суверенітету України та складної ситуації в економіці. Увага зосереджена навколо питань створення інноваційної моделі розвитку оборонно-промислового комплексу, що повинна послугувати імпульсом інтенсифікації діяльності ОПК України. Визначено необхідні заходи державної підтримки для підприємств ОПК України під час кризових явищ в економіці, проаналізовано господарсько-правові засоби оптимізації діяльності ОПК України в умовах постійної необхідності забезпечення армії озброєнням і військовою технікою. // The article analyzes economic and legal measures to reform the defense of Ukraine in a crisis situation in the Ukrainian economy, taking into account the challenges that arise as a result of external military aggression against the sovereignty of Ukraine and a difficult situation in the economy. Attention focuses around the issues of creating an innovative model of development of a defense-industrial complex, which should be served by an impulse of intensifying the ACCA. The necessary state support measures for Ukraine's defense enterprises during crisis phenomena in the economy are analyzed by economic and legal means of optimizing the activity of the military-industrial complex of Ukraine in the conditions of a constant need to provide armaments with weapons and military equipment. Key words: defense-industrial policies, economic and legal means of reforming the defense industry, military-industrial complex of Ukraine
Keywords: оборонно-промислова політика; господарсько-правові засоби реформування оборонної промисловості; ОПК України; defense-industrial policies; economic and legal means of reforming the defense industry; military-industrial complex of Ukraine